Pengaruh Influencer dan E-WOM terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan sebagai Variabel Mediasi Pada Pelanggan TikTok Shop - Nawang Nawastuti; Irmawati (SAFE-Network, 2023)
This research aims to determine the influence of Influencers and E-WOM on Customer Loyalty through Customer Satisfaction as a Mediating Variable for TikTok Shop Customers. In recent years, TikTok Shop has been widely used by Indonesian people to shop online. This increases the sales volume at the Tiktok Shop. This research is a quantitative research involving 150 respondents who are TikTok Shop users. The data in this research was collected using a questionnaire via Google Form which uses a Likert scale. The analysis technique used in this research uses Partial Least Square (PLS) data analysis techniques with the SmartPLS 3.2 program. The results of this research show that Influencers and E-WOM have a positive and significant effect on Customer Loyalty and Customer Satisfaction. Influencers and E-WOM have a significant effect on Customer Loyalty through Customer Satisfaction as a mediating variable.